Hematologic, biochemical, and infection biomarker abnormalities associated with COVID-19: A systematic review and meta-analysis - Abdulla, Sara; Elamami, Adela; Elawamy, Hayam; Muhammed, Aisha (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Objectives: We aimed to analyze the laboratory data of coronavirus disease 2019 (COVID-19) patients for clinical help, to overcome the vulnerabilities of reverse transcription–polymerase chain reaction testing for diagnosing COVID-19, and to reduce the number of negative results when diagnosing, particularly in global regions which are recognized to have limited resources. Materials and Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, the authors performed a systematic literature review, using three databases to assess laboratory data of COVID-19-confirmed cases, and the articles that described significant laboratory irregularities were ultimately chosen. Crosschecking was performed on the references of these articles in order to identify further studies. The statistical software R version 3.6.1 was used for meta-analysis of COVID-19 studies. Results: A total of 13 relevant articles were included. They yielded a total of 2662 individuals who tested positive for COVID-19. The analysis results demonstrated that male patients comprised a more substantial proportion, accounting for 57.9% of the total. The principal laboratory findings of the COVID-19 patients indicated that they commonly had lymphocytopenia 0.943 (confidence interval [CI]: 0.857–1.03), high D-dimer 0.459 (CI: 0.237–0.6808), high procalcitonin 0.089 (CI: 0.066–0.111), high C-reactive protein 17.203 (CI: 6.520–27.886), and high lactate dehydrogenase 278.265 (CI: 238.995–317.535). Conclusions: Infection with COVID-19 is associated with significant laboratory irregularities. The increased focus must be applied to laboratory parameters to quickly identify a large number of infected patients and asymptomatic carriers, prevent virus transmission, and assure timely treatment of patients, particularly in regions characterized by limited resources.
Keywords: A systematic review; coronavirus disease 2019; laboratory findings